The Platonizing Sethian Background of Plotinus's Mysticism - Mazur, Zeke (Nag Hammadi and Manichaean Studies, 2020)
Intro -- Contents -- Editor's Preface to the Present Volume -- Author's Acknowledgments -- Editor's Note on References, Editions, and Translations -- Abbreviations -- Tables -- Author's Preface -- Chapter 1 Introduction: The Gnostic Background of Plotinus's Mysticism -- 1 The Fundamental Problem of Plotinian Mysticism -- 2 Problems with the Prior Scholarship on Plotinian Mysticism -- 3 Platonizing Sethian Visionary Ascent and the Historical Context of Plotinian Mysticism -- 4 The Current State of the Research -- Chapter 2 The Structure of Plotinus's Ascent to Mystical Union with the One -- 1 Introduction -- 2 Phase A: Catharsis -- 3 Phase B: Mystical Self-Reversion -- 4 Phase C: Autophany -- 5 Excursus: A First Meditation on the Identity of the Mystical Subject -- 6 Phase C2: Self-Unification -- 7 Phase D: Annihilation -- 8 Excursus: Second Meditation on the Identity of the Mystical Subject -- 9 Excursus: On Beauty -- 10 Phase E: Union with the One -- 11 Vision and Light -- 12 Ennead VI.9[9].11.22-25 [See Complete Passage in Appendix A8] -- 13 Ennead VI.7[38].36.10-26 [Appendix A16] -- 14 Ennead V.3[49].17.28-38 [Appendix A19] -- 15 Excursus on V.3[49].17-28 -- 16 Ennead V.5[32].8.18-21 [Appendix A12] -- 17 Convergence of Center-Points -- 18 Sexual Intercourse -- 19 Excursus on VI.7[38].35.23-32 -- 20 Rapture or Spatial Displacement -- 21 Excursus on VI.7[38].35.36-40 -- 22 Excursus on VI.7[38].36.15-18 -- 23 Cultic Praxis -- 24 Phase E2: Desubjectification -- 25 Conclusion -- Chapter 3 The Identity of Prenoetic and Hypernoetic Subjectsin Plotinus -- 1 Introduction -- 2 Plotinian Ontogenesis -- 3 The Identity of the Hypernoetic Subject with the Prenoetic Efflux -- 4 The Convergence of Prenoetic and Hypernoetic Ecstasy -- 5 Conclusion.